2019
DOI: 10.1016/j.ijinfomgt.2019.01.008
|View full text |Cite
|
Sign up to set email alerts
|

The battle of Brain vs. Heart: A literature review and meta-analysis of “hedonic motivation” use in UTAUT2

Abstract: Much of the scholarly debate on the extrinsic-intrinsic motivation dichotomy to date has focused on organisational context. However, the recent upsurge of technology use amongst individuals in non-organisational context has led to consumer-focused research model such as extended unified theory of acceptance and use of technology (UTAUT2). The objective of this study is to bring back much needed focus on motivation dichotomy from the consumer perspective. This involved a systematic review and meta-analysis of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
132
2
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 248 publications
(185 citation statements)
references
References 105 publications
7
132
2
3
Order By: Relevance
“…The four studies that reported nonsignificant values were more focused on utilitarian value of consumers rather than hedonic motivation such as learning management system (Ain et al 2016), online air ticket purchases (Tomás Escobar-Rodríguez and Carvajal-Trujillo 2013), medical respondent samples in wearable healthcare technology (Gao et al 2015a) and mobile payment (Oliveira et al 2016). Therefore, researchers should be circumspect of using HM➔BI path relationship in studies focused on utilitarian value (Tamilmani et al 2019).…”
Section: Top Five Utaut2 Path Relationshipsmentioning
confidence: 99%
“…The four studies that reported nonsignificant values were more focused on utilitarian value of consumers rather than hedonic motivation such as learning management system (Ain et al 2016), online air ticket purchases (Tomás Escobar-Rodríguez and Carvajal-Trujillo 2013), medical respondent samples in wearable healthcare technology (Gao et al 2015a) and mobile payment (Oliveira et al 2016). Therefore, researchers should be circumspect of using HM➔BI path relationship in studies focused on utilitarian value (Tamilmani et al 2019).…”
Section: Top Five Utaut2 Path Relationshipsmentioning
confidence: 99%
“…Hedonic motivation plays a key role in determining technology acceptance and use (Brown & Venkatesh, 2005). The emphasis on technology for organizational users has moved to consumers, which is from extrinsic motivation to intrinsic motivation (Tamilmani, Rana, Prakasam & Dwivedi, 2019). It is referred to as the willingness and motivation to use a technology as a result of the pleasure gained from aesthetic and emotional feelings such as love and joy.…”
Section: Hedonic Motivationmentioning
confidence: 99%
“…Kizgin et al 2018;Shareef et al 2018) provide valuable insights into factors affecting intention to purchase within the boundaries of the contexts studied but it is difficult to generalise them. Meta-analysis addresses issues of generalisability across contexts by integrating the results of existing studies (Eden 2002;Ismagilova et al 2019;Pan et al 2012;Patil et al 2018;Tamilmani et al 2019). Meta-analysis is gaining attention from scholars in eWOM research, but most of the existing meta-analysis studies on eWOM communications focus on how eWOM communications affect sales (e.g.…”
Section: Introductionmentioning
confidence: 99%